Development and Validation of High Performance Liquid Chromatography Method for Simultaneous Estimation of Ambroxol and Doxofylline in Their Combined Tablet Dosage Form. (25th July 2013) - Singhal, Neha; Gaur, Kalpesh; Singh, Anoop; Sekhawat, Karni Singh
Abstract : The present study described a new, simple, accurate, and precise high performance liquid chromatography method for the simultaneous determination of Ambroxol and Doxofylline in combined tablet dosage form. The chromatographic method was standardized using a BDS hypersil C18, 250 mm × 4.6 mm, 5 μ (particle size), Thermo scientific from Germany with isocratic conditions, and mobile phase containing potassium dihydrogen orthophosphate buffer-pH 4.5 (0.05 M KH2 PO4 ): acetonitrile (60 : 40) at flow rate of 1 ml/min using UV detection at 254 nm. The retention times of Ambroxol and Doxofylline were 3.510 min and 7.247 min, respectively. The method was linear over the concentration range for Ambroxol 3.75–11.25 μ g/mL and for Doxofylline 50-150 μ g/mL. The recovery of Ambroxol and Doxofylline was found to be in the range of 99.42–101.18% and 99.37–100.28%, respectively. The validation of method was carried out using ICH guidelines. The described HPLC method was successfully employed for the analysis of pharmaceutical formulations containing combined dosage form.